Treatment outcomes for adolescent ectodermal dysplasia patients treated with dental implants - I. P. SWEENEY, J. W. FERGUSON, J. W. FERGUSON, & J. O. LUCAS (Paediatric Dentistry, 2005)
To evaluate dental implant survival in patients with ectodermal dysplasia (ED). T